Induction of cellular autophagy impairs TGF-β1-mediated extracellular matrix deposition in primary human knee fibroblasts - Oliver B. Dilger; Mason F. Carstens; Cole E. Bothun; Ashley N. Payne; Daniel J. Berry; Joaquin Sanchez-Sotelo; Mark E. Morrey; Roman Thaler; Amel Dudakovic; Matthew P. Abdel (Bone & Joint Research)
Aims: To evaluate the role of autophagy in primary knee fibroblasts undergoing myofibroblast differentiation as an in vitro model of arthrofibrosis, a complication after total knee arthroplasty characterized by aberrant intra-articular scar tissue formation and limited range of motion. Methods: We conducted a therapeutic screen of autophagic-modulating therapies in primary human knee fibroblasts undergoing transforming growth factor-beta 1 (TGF-β1)-mediated myofibroblast differentiation. Autophagy was induced pharmacologically with rapamycin or by amino acid deprivation. Picrosirius red staining was performed to quantify collagen deposition. Reverse transcription-quantitative polymerase chain reaction (RT-qPCR) and western blotting were conducted to evaluate fibrotic gene expression levels. Results: Rapamycin, an mTOR complex 1 (mTORC1) inhibitor and autophagy inducer, reduced TGF-β1-mediated collagen deposition. Interestingly, we simultaneously report that myofibrogenic genes, including ACTA2, were highly upregulated following rapamycin-TGF-β1 treatment. When autophagy was induced through amino acid deprivation, we demonstrated suppressed extracellular matrix levels, fibrotic gene expression (e.g. ACTA2), and SMAD2 phosphorylation levels in TGF-β1-stimulated fibroblasts. Conclusion: Our findings demonstrate that the induction of cellular autophagy suppresses TGF-β1-induced collagen deposition in primary human knee fibroblasts. Taken together, these data suggest that cellular autophagy may be prophylactic against the pathogenesis of arthrofibrosis. Cite this article: Bone Joint Res 2025;14(4):328–337.